A case report of atypical nodular cutaneous lupus mucinosis. Issue 49 (December 2017) - Wang, Na; Shan, Xiaofeng; Wu, Weizhi; Shen, Xiaoting; Hu, Tim Xiaoming; Pei, Zhenhuan; Wang, Keyu
Abstract: Rational: Nodular cutaneous lupus mucinosis is regarded as a distinctive cutaneous mucinosis deposition with systemic lupus erythematosus(SLE). All typical cases occurred as asymptomatic cutaneous papules, nodules, or plaques on the trunk, upper and lower extremities, and face. Histopathology is mainly revealed abundant mucin deposits among splayed collagen bundles in the dermis. At the same time we can find A the typical clinical manifestations and biological evidence of SLE. Here, we report the first case of nodular cutaneous lupus mucinosis that did not present with any prior symptoms or history of SLE. Patient concerns: We report the first case of nodular cutaneous lupus mucinosis that did not present with any prior symptoms or history of SLE. The patient was 34 years old. One year before admission, nodules began to appear on the elbows, chest, and back, and 2 months before admission erythema occurred on the face. Other notable clinical symptoms were not observed and had no prior history of SLE. Diagnoses: Initially, this patient was misdiagnosed by other clinics as having eczema. After histopathological assessment of skin biopsy and examination of antinuclear antibody signals, the patient was correctly diagnosed with nodular cutaneous lupus mucinosis. Interventions: Followed administration of systemic steroids and hydroxychloroquine. Outcomes: the eruptions quickly disappeared and laboratory indicators improved. Lessons: This case highlights the need for diagnostic vigilance in cases involving papules and nodules initially developing on the chest and elbows in the absence of obvious lupoid symptoms. We recommend a lower threshold for performing histopathological analysis and examination of antinuclear antibody signals in view of the rare but serious possibility of nodular cutaneous lupus mucinosis.